Predicting early mortality in resectable pancreatic adenocarcinoma: A cohort study. Issue 11 (11th February 2015) - Sohal, Davendra P.S.; Shrotriya, Shiva; Glass, Kate Tullio; Pelley, Robert J.; McNamara, Michael J.; Estfan, Bassam; Shapiro, Marc; Wey, Jane; Chalikonda, Sricharan; Morris‐Stiff, Gareth; Walsh, R. Matthew; Khorana, Alok A.
<x xml:space="preserve">Abstract</x> BACKGROUND Survival after surgical resection for pancreatic cancer remains poor. A subgroup of patients die early (<6 months), and understanding factors associated with early mortality may help to identify high‐risk patients. The Khorana score has been shown to be associated with early mortality for patients with solid tumors. In the current study, the authors evaluated the role of this score and other prognostic variables in this setting. METHODS The current study was a cohort study of patients who underwent surgical resection for pancreatic cancer from January 2006 through June 2013. Baseline (diagnosis ±30 days) parameters were used to define patients as high risk (Khorana score ≥3). Statistically significant univariable associations and a priori prognostic variables were tested in multivariable models; adjusted hazard ratios (HR) were calculated. RESULTS The study population comprised 334 patients. The median age was 67 years, 50% of the study population was female, and 86% of the patients were white. The pancreatic head was the primary tumor site for 73% of patients; 67% of tumors were T3 and 63% were N1. The median Khorana score was 2; 152 patients (47%) were determined to be high risk. Adjunctive treatment included chemotherapy (70%) and radiotherapy (40%). The postoperative (30‐day) mortality rate was 0.9%. The 6‐month mortality rate for the entire cohort was 9.4%, with significantly higher rates observed for high‐risk patients (13.4% vs 5.6%; P = .02). On multivariable analyses (examining a total of 326 patients), the Khorana score (HR for high risk, 2.31; P = .039) and elevated blood urea nitrogen (HR, 4.34; P<.001) were associated with early mortality. CONCLUSIONS Patients at high risk of early mortality after surgical resection of pancreatic adenocarcinoma can be identified using simple baseline clinical and laboratory parameters. Future studies should address preoperative interventions in these patients at high risk of early mortality. Cancer 2015;121:1779–1784. © 2015 American Cancer Society.